Developing Students' Motivation in Learning Engliah Vocabulary Through Synonym and Antonym Quiz at SMAN 9 Tana Toraja - Patricia Rahayu Tarbun Tarbun; sahril; Abdullah (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Quiz are activities with rules, goals and elements of fun so they are interesting for students. Students can learn, while students play. This can brighten up the class and bring more variety into language lessons This thesis aims to determine whether the use of synonym and antonym quizzes improves the vocabulary and motivation of first-year students at SMAN 9 Tana Toraja. This study used a quasi-experimental method using cluster random sampling technique. The population of this study was 57 students consisting of two classes. Class X.5 was chosen as the control class consisting of 29 students and Class X.4 was chosen as the experimental class consisting of 28 students. The instruments of this study were vocabulary tests through pre-test and post-test and questionnaires to measure student motivation in the experimental class. The results of this study indicate that using synonym and antonym quizzes can improve vocabulary in the experimental class. The pre-test score was